A process approach to harnessing crowd-sourcing for new product development. (1st January 2013) - Jagoda, Kalinga; Maheshwari, Bharat; Roy, Daniel
Small businesses face several difficulties in raising money for financing their new product development (NPD) efforts. This paper, through a case study, explores and examines the process of using crowd sourcing for financing NPD projects. We analyse the innovative steps taken by a small business to formulate and execute a successful crowd funding campaign. Crowd funding illustrated in this case as a NPD funding approach is a derivative of crowd sourcing. This approach if run successfully, can provide small businesses not only a chance to both display their ideas to their customers and supporters but also receive financial support from them for NPD through small contributions.